The Effect of Polarization Flipping Point on Polarization Dynamics by Optical Feedback Technique - Ehsan Ali Abed; Jassim Mohammed Najim; Suaded Salman Ahmed (Iraqi Journal of Science, 2021)
The effect of the optical feedback on the polarization flipping point and hysteresis loop was studied. The polarization flipping occurred at all angles between the polarizer axis and the laser polarization. The polarization flipping point changed by an optical feedback occurred at angles from 0° to 90°. Ability of choosing or controlling the laser polarization was determined by changing the direction of vertical and horizontal polarization by polarizer rotation in the external cavity from 0° to 90°.